Muon study of molecular magnets, spin crossover and magnetic nanodiscs - Blundell, S; Pratt, F; Marshall, I; Steer, C; Hayes, W; Letard, J; Heath, S; Caneschi, A; Gatteschi, D (2003)
We present the results of recent muon-spin rotation (muSR) experiments on a variety of novel molecular magnetic systems. Muons are sensitive to local static fields and magnetic fluctuations, but can probe much more than just the onset of long-range magnetic order. The spin-crossover phenomenon has been studied in Fe(PM-PEA)(2)(NCS)(2), which shows Gaussian and root-exponential muon relaxation in the high-spin and low-spin phases, respectively. Dy spin fluctuations have been studied with muSR in the ferrimagnetic chain Dy(hfac)(3)(NITEt). Experiments on a disc-shaped molecular complex containing Fe-19 (with spin 31/2) reveal the effects of quantum tunneling of magnetization and allow an estimate of the quantum tunneling rate. (C) 2002 Elsevier Science B.V. All rights reserved.